Southwest view of the principal quadrangle or court yard of Crosby Hall - Nash, F.; Rawle, Samuel (Tufts Archival Research Center, 2008)
Restored to its original state. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.